Manajemen Sumber Daya Aparatur Inspektorat Kabupaten Kediri Dalam Mewujudkan Good Governance - Retnosari, Veronica Lucky; Muhlasin, Muhlasin (Universitas Islam Kadiri, 2025)
This research aims to describe the management of Inspectorate apparatus resources and the factors that influence the management of apparatus resources as well as describe the steps for implementing regional guidance and supervision policies towards regional apparatus in realizing good governance. Data was obstained from interviews, observation and documentation. The research results show that the Kediri Regency Inspectorate in realizing good governance has strenghthened supervision by increasing apparatus resources through a management function approach including planning, organizing, directing and supervising. Factors that influence include infrastructure, adequate budget for increasing competence, routine and mandatory tasks and increasing the capabilities of the Inspectorate. The Kediri Regency Inspectorate has implemented regional guidance and supervision policies for regional officials into the Annual Supervision Work Program every year.